Fabrication of Nanofiltration Membrane based on Polyvinyl Alcohol Nanofibers Reinforced with Cellulose Nanocrystal using Electrospinning Techniques - Heru SB Rochardjo; Fatkhurrohman; Ahmad Kusumaatmaja; Ferriawan Yudhanto (International Journal of Technology, 2021)
Filtration is an effective method in any process concerning the removal of potential infective substances via a size separation mechanism. The filter can be made from various materials. This research analyzes the fabrication of nanofiltration membranes made from polyvinyl alcohol (PVA) nanofibers reinforced with ramie cellulose nanocrystal (CNC) using the electrospinning method. The physical and mechanical properties of the filters were investigated with varying CNC concentrations in PVA to investigate the effect of the CNC content. The results showed that the fiber diameter in the membranes was not significantly related to the CNC content. However, the strength and elongation increased with an increase in CNC concentration until a certain value was reached, at which point it started decreasing. The SEM image showed that the membrane nanofibers have a pore size small enough to be used in a nanofiltration process. SEM-EDX and TGA/DSC testing were also carried out to determine the elements in the membrane and show the suitability of the thermal resistance.